Design Embodiments Using Squeeze-Film Phenomenon to Attain Complete Separation of Contacting Surfaces - Mares, Cristinel; Atherton, Mark; Miyatake, Masaaki; Stolarski, Tadeusz (European Journal of Computational Mechanics, 2020)
In this paper four design embodiments that employ SFL to separate surfaces are explored. Section 2 details the fundamental principles of levitation based on SFL and associated Navier-Stokes equations. Section 3 describes four design embodiments utilising squeeze-film mechanism, namely a journal bearing, flexible frame, plain levitating plate and a non-contact gripper, in terms of their analytical description plus experimental and numerical results. Section 4 concludes the paper. The paper demonstrates that the squeeze-film levitation is a feasible idea and can be implemented by a number of different embodiments. The mechanism of levitation is quite complex, and its computer modelling requires advanced numerical methods. All designs presented have been numerically modelled and the outcomes experimentally validated, which can be considered as the main contribution of this article.